The Functional Role of Sphingosine Kinase 2 - Diaz Escarcega, Rocio; McCullough, Louise D.; Tsvetkov, Andrey S. (Frontiers in Molecular Biosciences, 2021)
Sphingosine-1-phosphate (S1P) is a bioactive lipid molecule that is present in all eukaryotic cells and plays key roles in various extracellular, cytosolic, and nuclear signaling pathways. Two sphingosine kinase isoforms, sphingosine kinase 1 (SPHK1) and sphingosine kinase 2 (SPHK2), synthesize S1P by phosphorylating sphingosine. While SPHK1 is a cytoplasmic kinase, SPHK2 is localized to the nucleus, endoplasmic reticulum, and mitochondria. The SPHK2/S1P pathway regulates transcription, telomere maintenance, mitochondrial respiration, among many other processes. SPHK2 is under investigation as a target for treating many age-associated conditions, such as cancer, stroke, and neurodegeneration. In this review, we will focus on the role of SPHK2 in health and disease.